Analisis Realisasi Anggaran Biaya Bagian Humas dan Protokoler Pada PT Pegadaian Kanwil XII Surabaya - Zhieren Adziqa As’ad; Anik Yuliati (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
. This research aims to analyze the realization of budget costs in the Public Relations and Protocol section at PT Pegadaian Kanwil XII Surabaya. In budget management, effectiveness and efficiency are very important to support company operations. This research uses a descriptive approach with qualitative and quantitative analysis methods, examining budget data and its realization during a certain period. The research results show that the budget experienced favorable deviations. The actual budget for the Public Relations and Protocol section is lower than the planned budget, which shows efficiency in spending without reducing the quality and effectiveness of the programs being implemented. Several factors contributing to this favorable deviation were identified, including effective use of technology, careful budget planning, and good internal oversight and controls. The conclusion of this research is that efficient budget management and tight supervision can produce profitable budget deviations.